(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
This review paper discusses Science, Technology and Innovation (STI) policy framework reform for developing countries by proposing three levels of policy integration process. In the last decade, there has been an increasing concern on the importance of STI for inclusive and sustainable economic growth. This paper aims to provide comprehensive understanding of the interdependence between governance processes and other stakeholders for leveraging STI policy at the grassroots levels. The attainment of national development goals requires realistic and context based policy development process based on relevant strategic approach at the grassroots. However, in many developing countries, there is a gap between policy and development priorities as most of them are not integrated into the grassroots. Based on the review of literature on STI policies, the analysis indicated that there is a need for a major policy reform for the third world countries’ STI polices in terms of policy agendas regarding to the sustainability dimensions. However, developing world still lacks the conceptualization of STI policy, which is tailed with their development goals. The prevalence of institutional and organizational fragmentation in developing countries is one major factor that constrained the technology transfer process from translation into the development of innovation initiative. The current body of research, however, is characterized by a narrow focus on the specific institutions like universities and research institutions but the bigger picture on STI policy interaction is largely ignored. The proposed framework STI policy ecosystem is organized around three different levels with multi actors ranging from global, regional and even national levels. The limitations of STI policies necessitate policy coordination, which opens significant challenges when it comes to the implementation endeavors. Lastly the paper brings out the establishment of institutional ecosystems at the grassroots in terms innovations and their subsequent absorptive technology capacities. And it is further argued that, this bottom-up approach of STI development is to pave the way towards achieving sustainable development goals. Therefore, this paper calls for more research on the context of STI framework reform, not only but particularly for the third world countries.